Penerapan Alat Bantu Penangkapan Ikan Pada Kelompok Nelayan Pole and Line di Desa Murante Kecamatan Suli Kabupaten Luwu - Malik, Andi Adam; Sahabuddin, Sahabuddin; Yushra, Yushra (PT. Riset Press International, 2024)
The objectives of this activity are: 1) To increase catch results and reduce operational costs through the implementation of fishing technology tools. 2) To enhance the capabilities of Pole and Line fishermen in using fishing tools such as GPS, Fish Finder, and the ability to independently read fishing catch maps. The method used in the implementation of Science and Technology for Society (IbM) activities is Participatory Rural Appraisal (PRA), which involves the community in the activities. The implementation of this activity includes counseling, training, demonstrations, and evaluations to assess the program's effectiveness, ensuring efficient socialization of the program. The implementation method involves applying and utilizing fishing tools (GPS, Fish Finder) for Pole and Line fishermen to determine fishing areas and capture fish according to the information on the fishing catch map issued by the Ministry of Marine Affairs and Fisheries of Indonesia. The results of this activity include the dissemination of information on the use of fishing technology tools, training in reading maps of potential fishing zones, and assistance in using the fish finder through counseling, direct practice, and interactive discussions to uncover issues and solutions that can be addressed by partners. In conclusion, the outcomes of the activity are: 1) Increased catch results and reduced operational costs through the implementation of fishing technology tools. 2) The desire and ability of Pole and Line fishermen to use fishing tools such as GPS, Fish Finder, and independently read fishing catch maps, subsequently inputting this information into the fishing tools